Modeling of rotary desiccant wheels - Harshe, Yogesh M.; Utikar, R. P.; Ranade, V. V.; Pahwa, D. (Chemical Engineering & Technology, 2005)
Rotary desiccant wheels are widely used in dehumidification and energy recovery applications. In this work, we have developed a 2D, steady state model of a rotary desiccant wheel. Mass and energy balance equations for the air streams and the desiccant wheels were developed. The hydraulic diameter and surface area for heat and mass transfer were calculated based on knowledge of the flute geometry. Appropriate correlations for the Sherwood number and Nusselt number were used to estimate heat and mass transfer coefficients. The model is capable of predicting steady state behavior of desiccant wheels having at the most three sections (process, purge, and regeneration). The mathematical model was validated using a real desiccant wheel, and the calculation results are in reasonable agreement with the experimental data. Based on this model, the temperature and humidity profiles in the wheel during both the dehumidification and the regeneration processes are analyzed. The simulated results were used to gain an insight into the operation of desiccant wheels. The model and the presented results will be useful for optimizing dehumidification and energy recovery applications.
Keywords: 1; 4-benzodioxan-2-carboxylate; 4-benzodioxan-2-carboxylic acid; doxazosin; enantio selectivity; enantiomeric ratio; ethyl 1; ethyl acetate; Lipases; transesterfication

Modeling of vaporization and cracking of liquid oil injected in a gas-solid riser - Nayak, S. V.; Joshi, S. L.; Ranade, V. V. (Chemical Engineering Science, 2005)
Vaporization and cracking of liquid oil injected in a gas-solid riser (fluid catalytic cracking riser reactor) was computationally studied in this work. Evaporation of a single drop injected in a stream of gas-solid mixture was analyzed first. A model for simulating evaporation of a drop considering heat transfer from the gas phase as well as from the solid particles was developed. The model relates the evaporation rate of droplet with rate of collisions of solid particles, specific heat capacities of solid and liquid, latent heat of vaporization, relative velocity of gas and liquid and temperatures of three phases. The understanding gained from such a model was then extended to simulate evaporation of liquid drops injected in FCC risers. The Eulerian-Lagrangian approach was used to simulate simultaneous evaporation and cracking reactions occurring in FCC riser reactors. A commercial CFD code, FLUENT (of Fluent Inc., USA) was used. Four and ten lump models were used for simulating cracking reactions. Appropriate user defined functions were developed to implement heterogeneous kinetics and heat transfer models in FLUENT. A special algorithm was developed to calculate accumulated coke on catalyst particles. A boiling point range was considered for simulating realistic oil feedstock. The model was first evaluated by comparing predicted results with published industrial data. The simulations were then carried out to understand influence of key design and operating parameters on performance of FCC riser reactors. The parameters studied included; initial oil droplet distribution, catalyst inlet temperature, catalyst to oil ratio and thermal cracking. The approach, model and results presented here would be useful for optimization of FCC operation, cost to benefit analysis of new FCC nozzles and related decision-making. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: cracking reactions; Evaporation; FCC; heat transfer; riser

Modeling of rotary cement kilns: applications to reduction in energy consumption - Mujumdar, Kaustubh S.; Arora, Amit; Ranade, V. V. (Industrial & Engineering Chemistry Research, 2006)
Rotary cement kilns are used for converting calcineous raw meal into cement clinkers. In this paper, we discuss and evaluate possible ways of reducing energy consumption in rotary cement kilns. A comprehensive one-dimensional model was developed to simulate complex processes occurring in rotary cement Kilns. A modeling strategy comprising three submodels. viz. a model for simulating the variation of bed height in the kiln, a model for simulating reactions and heat transfer in the bed region, and a model for simulating coal combustion and heat transfer in the freeboard region, was developed. Melting and formation of coating within the kiln were accounted for. Combustion of coal in the freeboard region was modeled by accounting for devolatilization, finite-rate gas-phase combustion, and char reaction. The simulated results were validated with the available data from three industrial kilns. The model was then used to understand the influence of various design and operating parameters on kiln performance. Several ways of reducing energy consumption in kilns were then computationally investigated. The model was also used to propose and to evaluate a practical solution of using a secondary shell to reduce energy consumption in rotary cement kilns. Simulation results indicate that varying kiln operating variables, viz. solid flow rate or RPM, can result only in small changes in kiln energetics. Use of a secondary shell over the kiln and energy recovery by passing air through the annular gap between the two appears to be a promising way to achieve significant energy savings. The developed model and the presented results will be useful for enhancing the performance of rotary cement kilns.

MgFeCe ternary layered double hydroxide as highly efficient and recyclable heterogeneous base catalyst for synthesis of dimethyl carbonate by transesterification - Nivangune, N. T. (Catalysis Letters, 2017)
A series of Mg3:Fex + Ce1−x LDHs (3:1) were synthesized by co-precipitation method by varying molar ratio of Fe:Ce between 1:0 to 0:1 (LDH-1 to LDH-6). All synthesized LDHs were characterized by XRD, FT-IR, TEM, N2 sorption, benzoic acid titration and XPS in detail and evaluated for selective synthesis of dimethyl carbonate by transesterification of ethylene carbonate with methanol. It was demonstrated that the structural and basic properties of synthesized LDHs were strongly dependent on the Fe:Ce molar ratio (Ce concentration). The correlation between their physicochemical properties and catalytic performance was studied in detail. Among all synthesized LDHs the best result was obtained with LDH-3 (Fe:Ce = 0.85:0.15) where LDH structure remained intact, and showed high number of strong basic sites on LDH surface. LDH-3 was recycled 7 times while maintaining high catalyst activity and selectivity towards DMC. The obtained results elucidate the important role of Ce in modifying the basic properties of LDH in enhancing the catalytic activity for DMC synthesis. Graphical Abstract: [Figure not available: see fulltext.]. © 2017, Springer Science+Business Media, LLC.
Keywords: Dimethyl carbonate; ethylene carbonate; Mg–Fe–Ce Ternary Hydrotalcite; transesterification

Modeling and simulation of a fluidized bed gasifier - Jain, A. A.; Mehra, A.; Ranade, V. V. (ASIA-Pacific Journal of Chemical Engineering, 2018)
A mathematical model to simulate continuous gasification of coal particles in a bubbling fluidized bed reactor is presented. Material and energy balance equations have been formulated based on the 2-phase theory. Well-known correlations have been used to estimate the hydrodynamics. Devolatilization, heterogeneous reactions, and homogenous reactions have been included in the model. The model is used to simulate 29 experimental data sets from the published literature. The model predictions agree very well with the experimental data by adjusting the particle size. After establishing agreement with the data, the model was used to investigate influence of various operating parameters on overall performance (carbon conversion and the gross calorific value of generated gas). Thermodynamic analysis (using the minimization of the Gibbs free energy approach) has also been discussed. The presented model and results provide useful tool and insight on design and operation of fluidized bed gasifier.